-(3y+3)-(-2y-6)=-1

Simple and best practice solution for -(3y+3)-(-2y-6)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3y+3)-(-2y-6)=-1 equation:


Simplifying
-1(3y + 3) + -1(-2y + -6) = -1

Reorder the terms:
-1(3 + 3y) + -1(-2y + -6) = -1
(3 * -1 + 3y * -1) + -1(-2y + -6) = -1
(-3 + -3y) + -1(-2y + -6) = -1

Reorder the terms:
-3 + -3y + -1(-6 + -2y) = -1
-3 + -3y + (-6 * -1 + -2y * -1) = -1
-3 + -3y + (6 + 2y) = -1

Reorder the terms:
-3 + 6 + -3y + 2y = -1

Combine like terms: -3 + 6 = 3
3 + -3y + 2y = -1

Combine like terms: -3y + 2y = -1y
3 + -1y = -1

Solving
3 + -1y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1y = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -1y = -1 + -3
-1y = -1 + -3

Combine like terms: -1 + -3 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 1/3(10x-6)=8 | | 6p-32-35=5 | | x+5=56 | | 3x^2+14x+31=0 | | x-2/2x^2-9x+10=0 | | -4x^2-11x-6=0 | | 1/2(c+8)=1/4c | | 2x-24=6x | | 8x+82=3x+2 | | 6ln(x^2-3)-7=12.2 | | 7+18r-3=6r+64-3r | | -12x-114=5x+11+8x | | -x^2-x+2=3x^2+10x+8 | | 8(y-3)=3y-59 | | 6(m-1/9)=55/12 | | x-4y=-25 | | 18-c+36=49 | | x+(x+35)+(2x-39)=592 | | 2(4d-6)=5d+12 | | x+13+1=44 | | 4k+4=2(k+5) | | 2/3x+1/9y=-19/27 | | 2.5x+10=1.5+17 | | 2r+4r=12 | | x+(x+100000)=600000000 | | 4y-19-y=-59+y | | -6-8(x+7)=-32-2x | | z/8=-6 | | -7x+26=6x | | 2x^3-19=12x | | x+13=44 | | (x^3+5x-18)/(x-2) |

Equations solver categories